The Effectiveness of Health Education on Self-Awareness of Diabetes Mellitus Patients in Reducing Blood Sugar Levels in Royal Prima Hospital Medan - Martha Silitonga; Putri Nurul Izzah Andini; Gading Widya Lestari; Giofanny Zega; Rizka Ayu; Tiarnida Nababan (Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetes mellitus affects public health at global, national, regional and local levels, as it is a non-communicable disease. Newly diagnosed patients and patients who have had diabetes mellitus for a long time differ in their level of self-awareness, so it is important to educate them on how to control blood sugar levels. The study aims to determine how effective health education is on self-awareness of diabetes mellitus patients in reducing blood sugar levels at RSU Royal Prima Medan in 2024. Quantitative research method with pre-experimental approach and one group pre-test and post-test design. The research sample involved 62 respondents. The results of the study using the Wilcoxom Sign Rank Test with a p-value of 0.000 <0.05 which indicates a significant relationship between health education and self-awareness of patients with diabetes mellitus in reducing blood sugar levels.